Does microcredit for the poverty-alleviated population have an income-increasing effect? Also on the "Raising the Low" effect. - Yin Liu; Lu Fan; Binjian Yan (PLoS ONE)
Promoting the continuous income increase of the poverty-alleviated population has become one of the key tasks to consolidate the achievements of poverty alleviation, promote rural revitalization and achieve common prosperity. Based on the survey data of 738 farmers in six poverty-alleviated counties (cities) in an underdeveloped region in northwest China, this paper uses the endogenous transformation regression model to empirically explore the income-increasing effect of microcredit for the poverty-alleviated population, and uses the quantile regression model and OLS regression model to explore raising the low effect of microcredit for the poverty-alleviated population. The results show that: (1) Based on the counterfactual hypothesis, if the farmers who obtain microcredit for poverty-alleviated population are not loaned, their production and operating income will decrease by 3.31%, that is, microcredit has a significant income-increasing effect, and the income-increasing effect of obtaining microcredit for the poverty-alleviated population on the monitoring objects is greater than the households that have lifted out of poverty. (2) The mechanism of action shows that the microcredit policy for the poverty- alleviated population promotes income increase by promoting farmers to increase material capital investment and social capital investment. (3) The income-increasing effect of obtain microcredit for poverty-alleviated population on the low-income initial endowment farmers is greater than that on high-income initial endowment farmers, and farmers with low-land initial endowment have a higher income increase effect, that is, a 'raising the low ' effect. The overall efficiency effect on 'low→high 'initial endowment farmers shows a decreasing trend. Therefore, in order to ensure the effectiveness of financial precision assistance, we should promote the microcredit policy of the poverty-alleviated population from the aspects of policy stability and implementation precision.